퇴적물 내 입도와 유기물 함량이 영양염류 및 중금속 농도에 미치는 영향 - 김석구(Seog Ku Kim); 이미경(Mi Kyung Lee); 안재환(Jae Hwan Ahn); 강성원(Sung Won Kang); 전상호(Sang Ho Jeon) (Daehan hwan'gyeong gonghag hoeji, 2005)
A study was carried out to identify the major causes of sediments pollution in the Paldang Lake in the vicinity of Gyeongan river. Samples from 40 sites were collected and analyzed to characterize the regional distributions of grain size, organic matter contents, and concentrations of T-N, T-P and heavy metals. contaminations. The mean grain size(Mz) ranged from sand type(Mz, $1{\sim}3\;φ$) where Bukhan River and Namhan River converges at a high flow rate to silt type(Mz, $5{\sim}10\;φ$) at the downstream of Gyeongancheon and Paldang lake, reflecting the water circulation in the area. Except sampling point St. 36 near the wetland, the determination coefficient($r^2$) of Mz and organic matter(LOI) was 0.88, showing that more organic matters are concentrated inside finer sediments. The concentrations of T-N and T-P in sediments were higher in the area at which Mz and organic matters are also higher. High concentrations of T-P analyzed in the sediments, ranging from $216{\sim}1,623\;μg/g$ (Avg. $769\;μg/g$) could be considered as a critical level. Adsorbed-P and NAI-P, which are easily released to the surrounding environments when physico-chemical characteristics of sediments are changed, was found to be around 20%, which was showed by the result of fractionated-P. Moreover, Principle Component Analysis(PCA), showed that high concentrations of T-N, T-P, organophilic metals (Cd, Cu, Pb, Zn) are distributed in the areas where high organic matter contents and fine grain-sized sediments are found. However, results of $I'_{geo}$ (Geoaccumulation Index) that considers the grain size of sediments showed that heavy metal concentrations in the lake was low enough to be considered as Class 1 indicating the relative degree of pollution was less than zero. 팔당호 표층퇴적물의 오염 특성을 파악하기 위해 경안천을 중심으로 팔당호 전반에 걸쳐 40개 지점에 대해 입도, 유기물 함량, 총질소, 총인, 중금속의 분포 특성을 분석하였다. 입도(Mz, mean grain size)의 분포 특성은 유입량 및 유속이 강한 북한강과 남한강 합류지점부터 팔당댐 지역에 걸쳐 사질(Mz, $1{\sim}3\;φ$)로 분포하며, 경안천 하부 및 팔당호 하부 지역에서는 세립한 silt(Mz, $5{\sim}10\;φ$)로 구성되어 이 지역의 수리 특성을 반영한다. 입도(Mz)와 유기물 함량(LOI)의 상관관계는 습지 근처인 St. 36을 제외하고, $r^2\;=\;0.88$로 세립토일수록 유기물 함량이 높아지는 경향을 보였다. 퇴적물 내 T-N과 T-P의 농도 역시 입도와 유기물 함량이 높은 지역에서 높은값을 나타내었다. 특히, T-P의 농도 분포는 $216{\sim}1,623\;μg/g$(Avg. $769\;μg/g$)의 범위로 팔당호 퇴적물내 인(phosphorus)의 오염이 심각한 것으로 나타났다. Fractionated-P를 통해 환경 변화에 의해 수체로 용출될 가능성이 큰 Adsorbed-P와 NAI-P(Non-apatite inorganic P)가 약 20%로 나타났다. 또한, 20개 항목의 결과를 토대로 통계학적 기법인 주성분 분석(Principle Component Analysis, PCA)을 실시한 결과, 입도가 세립하고, 유기물 함량이 높은 지역에서 T-N, T-P, 친유기성 중금속(Cd, Cu, Pb, Zn)이 높게 분포하는 것으로 나타났다. 그러나 중금속 오염 정도는 입도를 고려한 $I'_{geo}$(Geoaccumulation Index)로 분석한 결과 상대적 오염도가 0 이하 및 Class 1에 속하는 것으로 나타나 중금속 오염은 없는 것으로 평가되었다.